2013
DOI: 10.1103/physrevb.88.174112
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric precursor behavior in PbSc0.5Ta0.5O3detected by fi

Abstract: A novel experimental technique, resonant piezoelectric spectroscopy (RPS), has been applied to investigate polar precursor effects in highly (65%) B-site ordered PbSc 0.5 Ta 0.5 O 3 (PST), which undergoes a ferroelectric phase transition near 300 K. The cubic-rhombohedral transition is weakly first order, with a coexistence interval of ∼4 K, and is accompanied by a significant elastic anomaly over a wide temperature interval. Precursor polarity in the cubic phase was detected as elastic vibrations generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 82 publications
(160 reference statements)
4
61
0
Order By: Relevance
“…The transition is now sharp with no frequency dispersion of the dielectric response, 45 Previous studies using transmission electron microscopy have shown that structural modulations and complex strain pattern exist in all PST samples examined, independent of their degree of order. [46][47][48][49] These structural modulations are related to the relaxor behavior in disordered PST as PNRs.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…The transition is now sharp with no frequency dispersion of the dielectric response, 45 Previous studies using transmission electron microscopy have shown that structural modulations and complex strain pattern exist in all PST samples examined, independent of their degree of order. [46][47][48][49] These structural modulations are related to the relaxor behavior in disordered PST as PNRs.…”
mentioning
confidence: 93%
“…23 Below 425 K the thermal expansion increases when tweed precursor ordering of the ferroelectric transition commences. 45 In the precursor regime the sample is locally polar similar to other ferroelectric materials like BaTiO 3 , 55 as well as alloys and ferroelastics. 51,52 Disordered PST is a RFE undergoing a spontaneous cubic-to-rhombohedral (P m3m to R3) phase transition at Curie temperature T c just below T m .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This was found to provide good descriptions of precursor softening of the shear modulus in PbMg 1/3 Nb 2/3 O 3 [141] and PbSc 0.5 Ta 0.5 O 3 [142], and it also describes softening ahead of the cubic-tetragonal transition in BaTiO 3 [143]. These models have been tested for PZTFN6 but neither provides a quantitative fit to the precursor softening.…”
Section: Precursor Softeningmentioning
confidence: 99%